Kemampuan Menulis Teks Prosedur Siswa Kelas VII-1 SMP Yas’A Sumenep - Olivia Ananda; Abelia Nur Hikmah; Fatimiyah Ratu Izzahroh; Aisyah Aisyah; Abdul Wahab (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to determine the writing ability of procedural texts of class VII-1 students of Yas'a Junior High School, Sumenep. This study uses a quantitative approach with a descriptive research type. The research subjects were 10 students. The data collection technique was carried out through a procedural text writing test with the theme "How to Make Instant Noodles". The assessment was based on five aspects, namely the suitability of content and theme, completeness of text structure, sequence of steps, use of linguistic rules, and spelling and punctuation. Data were analyzed using descriptive statistical techniques in the form of calculating the average value (mean), the highest and lowest values, frequency, and percentage of each category. The results showed that the average value of students' procedural text writing ability was 82.5 which is included in the good category. The highest value obtained by students was 95, while the lowest value was 70. Based on the assessment categories, 2 students (20%) were in the very good category, 7 students (70%) were in the good category, and 1 student (10%) was in the sufficient category. Thus, the writing ability of procedural texts of class VII-1 students of Yas'a Junior High School, Sumenep is classified as good.